2014
DOI: 10.1074/jbc.m114.573519
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-mediated Mitochondrial Reactive Oxygen Species Metabolism Augments Wnt/β-Catenin Pathway Activation to Facilitate Cell Differentiation

Abstract: Background: Dissociation of the Wnt/β-catenin pathway effector Dishevelled from its complex with nucleoredoxin is a redox-sensitive process, yet the ROS sources remain elusive.Results: Mitochondrial Ca2+ influx stimulates endogenous ROS production and mediates Wnt/β-catenin pathway activity.Conclusion: Ca2+-mediated ROS production modulates the signaling efficiency of the Wnt/β-catenin pathway.Significance: Metabolic states influence fundamental and developmental signaling to drive cell differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
124
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(134 citation statements)
references
References 51 publications
9
124
1
Order By: Relevance
“…Rharass and colleagues demonstrated that the primary trigger for neuronal differentiation upon growth factor depletion in human neural progenitor cells is the generation of mROS. Interestingly, they reported that after growth factor depletion mROS reached a maximum increase of ~200% at 1 h and this increase was significantly but not completely restored at 3 h (no further time points were tested) [24]. Results from Xavier and colleagues are in agreement with our findings, also reporting a transient increase in superoxide mROS 1 h after the induction of NSC differentiation [27].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Rharass and colleagues demonstrated that the primary trigger for neuronal differentiation upon growth factor depletion in human neural progenitor cells is the generation of mROS. Interestingly, they reported that after growth factor depletion mROS reached a maximum increase of ~200% at 1 h and this increase was significantly but not completely restored at 3 h (no further time points were tested) [24]. Results from Xavier and colleagues are in agreement with our findings, also reporting a transient increase in superoxide mROS 1 h after the induction of NSC differentiation [27].…”
Section: Discussionsupporting
confidence: 82%
“…Notably, our data is in accordance with other processes reported to occur at early stages of ROS-induced NSC differentiation, namely Dvl dissociation and β-catenin activation [24].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…32,33 Treatment of S34F-expressing cells with the NOX1/4-specific inhibitor GKT137831 or with the pan-NOX inhibitor DPI profoundly reduced ASC oligomerization and thereby NLRP3 inflammasome assembly; thus, NLRP3 activation in response to SGMs is NOX1/4 dependent ( Figure 7B). Moreover, elevated levels of ROS in U2AF1-S34F cells were abrogated by GKT137831 or DPI treatment ( Figure 7N-O).…”
Section: Org Frommentioning
confidence: 99%
“…[32][33][34][35][36] Thus, we hypothesized that ROS generated by either S100A9 or somatic gene mutations (SGMs) would direct activation of b-catenin in MDSs. In accordance with this, the mean percentage of ROS positive cells was increased 16.5-fold in MDS BM-MNCs (n 5 5) compared with normal donors (n 5 2) (P 5 .011) ( Figure 6A), with corresponding significant increases in ROS MFI (P 5 .028) ( Figure 6B).…”
Section: S100a9 and Mds Sgms Trigger Pyroptosis And B-catenin Activatmentioning
confidence: 99%